2018
DOI: 10.1098/rspa.2018.0492
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust nanoparticles and their behaviour in the atmosphere

Abstract: Diesel engine emissions are by far the largest source of nanoparticles in many urban atmospheres, in which they dominate the particle number count, and may present a significant threat to public health. This paper reviews knowledge of the composition and atmospheric properties of diesel exhaust particles, and exemplifies research in this field through a description of the FASTER project (Fundamental Studies of the Sources, Properties and Environmental Behaviour of Exhaust Nanoparticles from Road Vehicles) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 86 publications
2
23
0
Order By: Relevance
“…Ultrafine particles occur in the urban environment either as primary emissions (e.g. from car exhaust, Harrison et al, 2018) or secondarily as the product of new particle formation (NPF) (Brines et al, 2015;Guo et al, 2014;Kulmala et al, 2017;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafine particles occur in the urban environment either as primary emissions (e.g. from car exhaust, Harrison et al, 2018) or secondarily as the product of new particle formation (NPF) (Brines et al, 2015;Guo et al, 2014;Kulmala et al, 2017;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The NP modeling showed that, when released from their host medium into the environment, they could have different compositions and properties such as size distribution and state of agglomeration. This implies that these unintentionally discharged NPs have an unforeseen and unpredictable impact on the environment and its inhabitants [ 146 ].…”
Section: Nanoparticles Emergencementioning
confidence: 99%
“…A notable exception is emissions from jet aircraft for which fuels still contain several hundred parts per million of sulfur, and emissions from major airports are detectable in the atmosphere in a number of major European cities at a considerable distance from the main point of emission [ 41 , 42 ]. Ultrafine particles from road traffic comprise both a soot mode of primarily graphitic carbon with a lesser amount of associated organic matter, and a nucleation mode which is primarily semi-volatile organic compounds condensed on the surface of a very small nucleus of sulfuric acid or inorganic ash derived from engine emissions [ 5 ]. The nucleated component has tended in the past to dominate particle number emissions, but the reduction in the sulfur content of road vehicle fuels, which took place in late 2007 in the UK and at similar times elsewhere in Europe, led to a very major reduction in particle number concentrations at roadside locations such as Marylebone Road [ 43 ].…”
Section: Ultrafine (Nano) Particlesmentioning
confidence: 99%